Agricultural literacy in artificial insemination and agribusiness management for social innovation in rural populations affected by armed conflict in Colombia - Lenis, Yasser Y.; Montgomery, Amy Jo; Carrillo-González, Diego F.; González-Palacio, Enoc Valentín; Barrios, Dursun; Elmetwally, Mohammed A. (Frontiers in Sustainable Food Systems, 2024)
The achievement of education in rural populations was one of the Millennium Development Goals (MDGs), outlined by the United Nations. During the last World Summit on Sustainable Development (WSSD), it was concluded that the majority of the world’s poor, illiterate and undernourished population lives in rural areas; therefore, access to education is considered one of the greatest challenges for governments in countries with developing economies. The purpose of this study was to determine how a theoretical-practical training program in rural management and leadership (D-ML), artificial insemination (D-AI), and bovine genetic improvement (D-GI) affected the perception and level of knowledge in a rural population affected by Colombia's armed conflict. Phase 1 included the theoretical and practical training of undergraduate animal sciences students in three dimensions (D-ML, D-AI, D-GI). After training, students were evaluated according to their level of theoretical-practical knowledge and their behavioral performance. There were 13 students selected to be a part of what we went on to call “the group of student leaders”. Phase 2 included the socioeconomic characterization and training of rural residents by the group of student leaders and field experts in the same three dimensions (D-ML, D-AI, D-GI). We evaluated the perception and level of knowledge before and after training in 63 rural residents using an evaluative instrument. The perception of knowledge in rural residents was low for general knowledge (GTD) (2.48±0.76, p ˂ 0.05), D-ML (2.89±1.18, p ˂ 0.05) and D-AI / D-GI (2.17±0.83, p ˂ 0.05), in accordance with the 5-point Likert-type ordinal scale. When level of knowledge was measured before the theorical-practical training, the level of GTD was 45.9%, however, after the training it increased to 77.6% (p<0.01), while the level of knowledge for D-AI increased from 38.5 % pre-training to 80.6 % (p ˂0.05) post-training, and level of knowledge for D-GI pre-training was 50.8% and increased to 73.0% (p<0.01) post-training. Finally, the level of knowledge for D-ML increased (p<0.01) from 54.8% pre-training to 75% post-training. Altogether, rural extension programs contribute to closing knowledge gaps in relation to the use of reproductive biotechnologies and bovine management in rural areas affected by armed conflict.